Effectiveness of Tending Activities in Broadleaved Forests - Odintsov, Maria Martynova, Rida Sultanova, Liubov Blonskaya, Aydar Gabdelkhakov, El'za Volkova, Georgiy (Journal of Environmental Accounting and Management, 2026)
The aim of the study is to assess the response of plantations in general and individual trees to thinnings of different intensity. The research target is forests located on the forestry fund lands of the Bashkortostan Republic. The research is based on the method of test areas used in complete enumeration and selection of sample trees of Tilia cordata Mill. There was conducted an analysis of variability of morphological characteristics of lime trees after thinnings of different intensity in young stands (from 50 to 75%). After cleaning from 1 to 10 shoots were on mother stumps. The analysis showed that thinnings have a direct impact on formation of trunks and crowns of target trees: low intensity thinning provides a strong variation (the crown length -- 21.2%, the crown projection diameter -- 37.9%), while high intensity cutting brings in less change (the crown length -- 11.7%, the crown projection diameter-- 18.0%). The felling intensity influenced the nature of flowering and distribution of flowers: on the plot with an intensity of 75% and 1 shoot on the stump, there is the highest occurrence of flowering trees -- 20.8%; while on the plot after thinning with 50% intensity and an average number of 10 shoots on the stump, 55.3% of trees didn't bloom. In general, there are 4.2-20.8% trees with very good flowering and uniform arrangement of flowers throughout the crown. Studies have found that thinning of young stands in aspen forests, located close to beekeeping apiaries, makes it possible to restock the plots with nectar plantations of predominantly small-leaved lime trees.